PENGARUH PERSEPSI DAN RELIGIUSITAS TERHADAP MINAT MASYARAKAT KABUPATEN BIMA MENJADI NASABAH DI BANK SYARIAH DENGAN PENGETAHUAN SEBAGAI VARIABEL MODERASI (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
The purpose of this study was to measure the factors that influence the interest of the people of Bima district to become customers with knowledge as a moderating variable. This research is a descriptive quantitative research by distributing questionnaires as a data collection method. The sample in this study was 100 respondents, namely people in Bima district. The data analysis technique used the STATA version 16 application. To see the results of the test the researchers used Moderated Regression Analysis (MRA). The results of the study show that the variables of perception and religiosity have no effect on interest in becoming a customer in Islamic banks. Then the Knowledge variable can moderate Perception and Religiosity towards Interest in Becoming a Customer in Islamic Banks. The results of this study are expected to be useful for financial institutions as a source of reference and information in making decisions and increasing public knowledge.